2022
DOI: 10.3390/cells11233743
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Detoxification of Insecticides by Potentially Probiotic Lactic Acid Bacteria Isolated from Honeybee (Apis mellifera L.) Environment—An In Vitro Study

Abstract: Lactic acid bacteria (LAB) naturally inhabiting the digestive tract of honeybees are known for their ability to detoxify xenobiotics. The effect of chlorpyrifos, coumaphos, and imidacloprid on the growth of LAB strains was tested. All strains showed high resistance to these insecticides. Subsequently, the insecticide binding ability of LAB was investigated. Coumaphos and chlorpyrifos were bound to the greatest extent (up to approx. 64%), and imidacloprid to a much weaker extent (up to approx. 36%). The insecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…In our study, we evaluated the acid profiles of 10 LAB strains isolated from different environments ( Figure 1 ). In previous publications, these strains demonstrated the most potent antagonistic activity against honeybee pathogens (e.g., Paenibacillus spp., Melissococcus plutonius ), insecticide detoxification capacity, and adhesion ability to various surfaces [ 26 , 27 , 28 ]. Additionally, A. kunkeei DSM12361 isolated from the honeybee gut microbiota was used as a reference strain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, we evaluated the acid profiles of 10 LAB strains isolated from different environments ( Figure 1 ). In previous publications, these strains demonstrated the most potent antagonistic activity against honeybee pathogens (e.g., Paenibacillus spp., Melissococcus plutonius ), insecticide detoxification capacity, and adhesion ability to various surfaces [ 26 , 27 , 28 ]. Additionally, A. kunkeei DSM12361 isolated from the honeybee gut microbiota was used as a reference strain.…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentrations of these acids were detected in CFS from P. pentosaceus 14/1, which in our previous study showed potent protective activity against chlorpyrifos, coumaphos, and imidacloprid [ 28 ]. Butyric acid and its derivatives exhibit anticancer properties, which may be related to the ability of P. pentosaceus 14/1 to reduce the cytotoxicity and genotoxicity of insecticides [ 28 , 61 , 62 ]. The only strain that did not produce propionic acid was A. kunkeei DSM 12361.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the selection of strains with detoxification potential can occur in natural habitats. For example, LAB isolated from the gut of bees exposed to pesticides such as chlorpyrifos, coumaphos, and imidacloprid are capable of binding and neutralizing them in vitro as well [ 140 ].…”
Section: Prospects In Fermented Food Detoxificationmentioning
confidence: 99%